Histopathological Diagnosis of Alopecia Clinically Relevant to Alopecia Areata - Lekhavat, Chinmanat; Rattanaumpawan, Pinyo; Tosti, Antonella; Korviriyakamol, Tarinee; Jerasutat, Suthep; Sudtikoonaseth, Poonnawis; Pattanaprichakul , Penvadee (Siriraj Medical Journal, 2023)
Objective: To study the histopathological diagnosis of alopecia clinically relevant to AA and to compare the histopathology between acute and chronic AA divided by time to onset at three and six months. Materials & Methods: We conducted a cross-sectional study of 113 patients with typical manifestation of AA. Two scalp biopsies were done horizontally and vertically to confirm diagnosis. Histological findings of AA in the acute group were subsequently compared with the chronic group. Results: Of the 113 eligible patients, 109 (96.5%) were pathologically diagnosed with AA. Other diagnoses included lichen planopilaris, lupus panniculitis, and unspecified scarring alopecia. The percentage of terminal telogen hairs in the acute group was significantly higher than the chronic group (mean % anagen: % telogen ratio = 21.2%:78.8% vs. 36.0%:64.0%; p = 0.016), while the chronic group had a significantly higher number of follicular streamers (mean ± SD; 2.5 ± 2.2 vs. 3.7 ± 2.6; p = 0.023). The number of vellus hairs significantly increased in the acute group at the six-month onset (p = 0.006). The number of nanogen hairs also increased significantly in the chronic group at both the three- and six-month onset (p = 0.020 and p = 0.007). Conclusion: Typical manifestations of AA are not always diagnosed as AA. Acute AA has more terminal telogens and vellus hairs, while chronic AA has more follicular streamers and nanogen hairs.